Bankruptcy Prediction Analysis of Media and Entertainment Subsector Industry in 2022-2024 Using Altman Z-Score Model - Rachelia, Michelle; Riny Jefri (CV. AFDIFAL MAJU BERKAH, 2025)
Tight business competition and changing times provide challenges for companies to always innovate and be more creative in order to survive and maintain the continuity of the business being run. This study aims to predict bankruptcy in four media and entertainment subsector companies in 2022-2024 using the modified Altman Z-Score model. The research objects used are PT Net Visi Media Tbk, PT Media Nusantara Citra Tbk, PT Surya Citra Media Tbk, and PT Visi Media Asia Tbk. The method used is descriptive quantitative research method. The data used is secondary data in the form of company financial reports obtained from the IDX. The results of the Z-score analysis in this study indicate that there are two companies that are indicated to experience bankruptcy, namely PT Net Visi Media Tbk and PT Visi Media Asia Tbk with a Z-score of less than 1.10 during 2022-2024 and there are two companies that are not indicated to experience bankruptcy, namely PT Media Nusantara Citra Tbk and PT Surya Citra Media Tbk with a Z-score of more than 2.60 during 2022-2024.